2017
DOI: 10.1155/2017/2163610
|View full text |Cite
|
Sign up to set email alerts
|

Combined Nonlinear Analysis of Atrial and Ventricular Series for Automated Screening of Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia in clinical practice. It often starts with asymptomatic and short episodes, which are difficult to detect without the assistance of automatic monitoring tools. The vast majority of methods proposed for this purpose are based on quantifying the irregular ventricular response (i.e., RR series) during the arrhythmia. However, although AF totally alters the atrial activity (AA) reflected on the electrocardiogram (ECG), replacing stable P-waves by chaot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
(123 reference statements)
1
13
0
Order By: Relevance
“…Using windows of seven beats from 20 records of the AFDB, the authors reported Se = 98.09% and Sp = 91.66%. On the contrary, Ródenas et al ( 2015 ) and Ródenas et al ( 2017 ) assessed the presence of the P-wave by measuring the wavelet entropy (WE) from the median TQ interval and the variability of the TQ interval series, respectively. For the former, the WE of 10 beats was used to make the detection with an average delay of 5 beats, resulting in Acc = 95.28%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using windows of seven beats from 20 records of the AFDB, the authors reported Se = 98.09% and Sp = 91.66%. On the contrary, Ródenas et al ( 2015 ) and Ródenas et al ( 2017 ) assessed the presence of the P-wave by measuring the wavelet entropy (WE) from the median TQ interval and the variability of the TQ interval series, respectively. For the former, the WE of 10 beats was used to make the detection with an average delay of 5 beats, resulting in Acc = 95.28%.…”
Section: Discussionmentioning
confidence: 99%
“…One problem when investigating P-wave morphology is dealing with noisy records. In fact, for the studies from Ladavich and Ghoraani ( 2015 ), Ródenas et al ( 2015 ), and Ródenas et al ( 2017 ) manual revision of the data was needed before running the experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 50 signals were discarded because they did not present any data. The remaining 250 ECGs were processed with an automatic algorithm to detect AF episodes within the clean ECG intervals [ 45 ] and later revised by an expert physician. Finally, the PDB comprises 36 single-lead ECG recordings lasting between 1 and 2 h from patients with intermittent AF which were recorded using a Nuubo™ textile wearable Holter.…”
Section: Databasesmentioning
confidence: 99%
“…The signals were recorded at a sampling frequency of 250 Hz and 12 bits of resolution over a dynamic range of ±5 mV. As before, an automatic algorithm was used to detect AF episodes [ 45 ], and two experts independently visualized the recordings to identify sufficiently clean and noisy intervals. ECG excerpts were labelled as noisy when either physician was unable to confidently distinguish all R-peaks.…”
Section: Databasesmentioning
confidence: 99%